THE INFLUENCE OF HARDINESS ON THE WELL-BEING FORMATION OF HIGHER MILITARY EDUCATION STUDENTS - Chernukha, N.; Kostenko, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article is devoted to the influence of hardiness on the well-being of students of higher military education. The relationship between social support and hardiness in improving the well-being of students of higher military education in modern realities is singled out. It was found that social support and resilience are important markers of social and psychological well-being. It has been established that developing social skills and signs of hardiness among students of higher military education is an important segment of the formation and development of well-being. Emphasis is placed on the fact that the influence of the hardiness of higher military education recipients is undeniably actualised in the conditions of war in Ukraine. It is noted that those who obtain higher military education with better social and psychological well-being achieve significant success in the educational process and professional and life self-realisation. It is emphasised that the students of higher military education are constantly faced with various life problems in today's socio-cultural conditions. Therefore, it is advisable to introduce into the educational process of institutions of higher military education, which prepare specialists in military specialities' training classes on the formation and development of life skills, which will positively affect the quality of professional training. Specific steps have been taken to analyse the influence of the hardiness of higher military education graduates on the quality of their professional activity in the conditions of modern realities. It is outlined that applicants of higher military education with a high level of vitality seek to influence the results of professional and life events, take an active part in them, try to learn constantly, and with a low level of hardiness, refuse particular life and professional events that they consider dangerous.
Keywords: social support, hardiness, well-being, students of higher military education, military specialties